The Ideal House in the Colony According to Ons Huis in Indie Book - Rahmia Nurwulandari; Yulia Nurliani Lukito (International Journal of Built Environment and Scientific Research, 2020)
A house is a building that serves as a place to live for the family. It should be comfortable and appropriate so the people inside the house could live well. To achieve that, people need knowledge about house decorating and how to manage a household. This paper discusses the household manual book entitled Ons Huis in Indie that written by a female Dutch writer, Johanna Catenius (1908). She promised the reader that they could make the comfortable house for the family after they read the manual book. This paper is focused in understanding the meaning of comfort that Catenius meant by examining the book through hermeneutics methods. It will answer the question: what has constructed the idea of creating comfort in Ons Huis in Indie? The purpose of this research is to discover the colonial thoughts by looking the house arrangement tips in the household manual book.